[OP.4B.02] KLOTHO SUPPLEMENTATION ATTENUATES BLOOD PRESSURE AND OXIDATIVE STRESS IN DIABETES. (September 2017) - Takenaka, T.; Kobori, H.; Inoue, T.; Miyazaki, T.; Suzuki, H.; Nishiyama, A.; Ishii, N.; Hayashi, M.
Abstract : Objective: Klotho interacts with various membrane proteins such as receptors for transforming growth factor (TGF)-β and insulin-like growth factor (IGF) to alter their function. We have recently demonstrated that exogenous klotho protein supplementation suppresses renin-angiotensin system (RAS) and hypertension in adriamycin nephropathy. Renal expression of klotho is diminished in diabetes. In the present study, the effects of klotho supplementation on diabetic nephropathy were assessed. Design and method: Recombinant klotho protein (0.2 μg/kg/day) or vehicle was administered daily by subcutaneous injection to db/db mice. Blood pressure was measured by tail-cuff methods. After 3 months, mice were killed by over-dose of anesthesia and the aorta and kidneys were harvested for the analysis. Results: Exogenous klotho protein supplementation reduced kidney weight (0.36 ± 0.03 vs. 0.28 ± 0.02 g, p < 0.05), systolic blood pressure (112 ± 3 vs. 105 ± 2 mmHg, p < 0.05), albuminuria (2.9 ± 0.6 vs. 1.8 ± 0.4 mg/day, p < 0.05) and 8-epi-prostaglandin F2αl excretion (410 ± 94 vs. 74 ± 41 ng/day, p < 0.01) without changes in body weight. Although klotho supplementation slightly increased glycated albumin from 1510 ± 60 to 1740 ± 70 μg/ml (p < 0.05), klotho reduced renal angiotensin II levels (202 ± 8 vs 126 ± 4 fmol/g.kidney.wt) associated with reduced renal expression of angiotensinogen. Klotho supplementation improved aortic and renal expression of superoxide dismutase (SOD), as well as renal klotho expression itself (p < 0.01 for each). Klotho reduced renal abundance of hypoxia-inducible factor 1 and renal expressions of TGF-β and fibronectin (p < 0.05 for each). Klotho supplementation diminished renal abundance of phosphorylated Akt and mTOR (p < 0.01 for each). Creatinine clearance and glomerular expression of nephrin were similar between klotho and control groups. Conclusions: The present data indicate that klotho supplementation reduces blood pressure and albuminuria in association with ameliorating RAS and fibrosis in db/db mice, similarly to adriamycin nephropathy. Furthermore, our results are consistent with the notion that klotho inhibits IGF signaling, inducing SOD to reduce oxidative stress and suppressing Akt-mTOR signaling to decrease abnormal kidney growth in diabetes. Finally, the present findings suggest that although klotho inhibits TGF-β signaling, it may increase insulin resistance, resulting in null effects on diabetic glomerulus, providing translational evidence that great cautions are required for glycemic control in applying klotho protein supplementation for diabetic nephropathy.